Cactus Pear Sheet and Pasteurized and Sterilized Cactus Pear Juices - El-Samahy, S. K.; Abd El-Hady, E. A.; Habiba, R. A.; Moussa-Ayoub, T. E. (Journal of the Professional Association for Cactus Development, 2008)
Orange-yellow cactus pear pulp was evaluated for some technological and chemical characteristics. The pulp was used to produce dehydrated cactus pulp sheet and pasteurized and sterilized cactus pear juices. A preliminary study was carried out to evaluate the effects of drying temperature (60 and 70ºC) and pulp thickness (5, 10, and 15mm) on the dehydration rate of cactus pear pulp. Cactus pear pulp was prepared for dehydration by adding different ratios of sucrose (0, 1, 2, 3, 4, 5, and 10%). The prepared pulps were dehydrated in an air oven, and then evaluated organoleptically. The most accepted sheets were those prepared with 2 and 3% sucrose. For cactus pear juices, pulp was mixed with sugar solution in a ratio of (1:1), and adjusted before thermal treatment at 15ºBrix and pH 5. This prepared juice divided into three parts, the first was pasteurized directly at 95ºC, the second was treated with 100 ppm sodium benzoate and then pasteurized at 95ºC, and the third was sterilized directly at 121ºC. Some technological, chemical, microbiological, and sensory characteristics of the three produced juices were evaluated during storage at room (28±5ºC) and refrigeration (8±2ºC) temperatures for six months. All produced juices were microbiologically stable for the storage period, and the pasteurized juices were the best organoleptically.